Reflections on the Professional Training and the Bond between Teacher (Master) and Apprentice (Móin-Móin - Revista de Estudios sobre Teatro de Formas Animadas, 2018)
This article reflects on a recurring question often in the field of professionaltraining on puppetry: is it possible to describe the content and form of making art inour art, and communicate through usual process of teaching and learning? How theexperienced artist, in his role of teacher, with the student or trainee is linked?Keywords: Transmigrate. Emptying. Póiesis-tekné. Manipulation-interpretation.